Reduced Order Extended Kalman Filter based Parameter Estimation for Induction Motor Drives - Rıdvan DEMİR; Murat BARUT (Gazi Üniversitesi Fen Bilimleri Dergisi, 2019)
In this study, a speed-sensored reduced-order extended Kalman filter (RO-EKF) based estimator is designed for direct vector control system of induction motors. The rotor resistance, stator resistance, and magnetizing inductance are simultaneously estimated by the designed estimator. The proposed estimator is tested by simulations for a wide speed range including very low/zerospeed and field-weakening zone, under the variations in rotor angular velocity, load torque, rotor resistance, stator resistance, and mutual inductance changes. Simulation results obtained from the proposed estimation algorithm and the speed-sensored direct vector control based induction motor drive utilizing the designed estimation algorithm are quite satisfactory. Also, the proposed estimation algorithm is known as the first RO-EKF algorithm in the literature which estimates the stator resistance, rotor resistance, and magnetizing inductance simultaneously